Notch1 primes CD4 T cells for T helper type I differentiation through its early effects on miR-29 - Chandiran, Karthik (Mol Immunol, 2018)
The transmembrane receptor, Notch1 plays an important role during the differentiation of CD4 T cells into T helper (Th) subsets in the presence of appropriate cytokines, including differentiation into Th1 cells. MicroRNAs have also been shown to be important regulators of immune responses, including negatively regulating cytokine production by Th1 cells. The miR-29 family of microRNAs can act to inhibit tbx21 and ifng transcription, two important pro-inflammatory genes that are abundantly expressed in Th1 cells. Here we show that Notch1 may prime CD4 T cells to be responsive to Th1-polarizing cues through its early repressive effects on the miR-29 family of microRNAs. Using a combination of cell lines and primary cells, we demonstrate that Notch1 can repress miR-29a, miR-29b, and miR-29c transcription through a mechanism that is independent of NF-κB. We further show that this repression is mediated by canonical Notch signaling and requires active Mastermind like (MAML) 1, but this process is superseded by positive regulation of miR-29 in response to IFNγ at later stages of CD4 T cell activation and differentiation. Collectively, our data suggest an additional mechanism by which Notch1 signaling may fine-tune Th1 cell differentiation.